Formulation and implementation of a practical multi-surface soil plasticity model. (January 2020) - Whyte, S.A.; Burd, H.J.; Martin, C.M.; Rattley, M.J.
Abstract: This paper presents a new constitutive model for clay, for undrained monotonic and cyclic loading, that has been developed specifically for geotechnical design applications. The model employs a parallel Iwan approach, consisting of multiple elastic-perfectly-plastic micro models. Degradation of stiffness and strength during cyclic loading is incorporated using an empirical cyclic overlay method. The theoretical framework and calibration processes for the model are presented. An implementation of the model in a commercial finite element program is then described; this implementation is demonstrated via 3D finite element analyses of example offshore monopile foundations subjected to monotonic and cyclic lateral loading.